2016
DOI: 10.3109/00365521.2016.1161066
|View full text |Cite
|
Sign up to set email alerts
|

The PNPLA3 rs738409 C > G polymorphism is associated with the risk of progression to cirrhosis in NAFLD patients

Abstract: In NAFLD patients, carriage of the PNPLA3G allele, and particularly of the GG genotype, is significantly associated with the risk of cirrhotic evolution. If confirmed in larger series, these results would suggest that most of NASH cases require the contribution of an altered PNPLA3 function to progress until cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 28 publications
0
14
0
1
Order By: Relevance
“…Indeed, the I148M variant has been associated with the degree of hepatic injury and all the histopathological aspects of NAFLD, including the presence of NASH, fibrosis, and development of HCC [ 5 , 22 ]. More recently, we have reported that the rs738409 PNPLA3 SNP is associated not only generically with NAFLD fibrosis but also specifically with the evolution to NASH cirrhosis [ 23 ]. To date, the rs58542926 SNP in the TM6SF2 locus should be considered in the second place of importance.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the I148M variant has been associated with the degree of hepatic injury and all the histopathological aspects of NAFLD, including the presence of NASH, fibrosis, and development of HCC [ 5 , 22 ]. More recently, we have reported that the rs738409 PNPLA3 SNP is associated not only generically with NAFLD fibrosis but also specifically with the evolution to NASH cirrhosis [ 23 ]. To date, the rs58542926 SNP in the TM6SF2 locus should be considered in the second place of importance.…”
Section: Discussionmentioning
confidence: 99%
“… 2015 China 11.81 ± 2.20 11.44 ± 2.99 162 865 23 Uygun, A [ 42 ]. 2017 Turkey 42.1 ± 11.4 34.1 ± 12.8 216 150 24 Valenti, L. [ 43 ] 2012 Italy 49.5 ± 12 48(1 ± 2 144 257 25 Valenti, L. [ 44 ] 2010 Italy 46.4 ± 11 48.4 ± 13 253 179 26 Vespasiani-Gentilucci, U [ 45 ]. 2016 Italy 51.5 ± 12.3 40.1 ± 13.1 60 125 27 Wang, C. W [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…[ 18 ] Additionally, recent studies revealed that this polymorphism was also associated with liver damage diseases such as NASH, fibrosis, cirrhosis, and hepatocellular carcinoma. [ 8 , 12 , 21 , 22 , 24 , 39 ] In order to show the involvement of rs738409 in other liver damages in our cohort, further studies are required with a larger group of patients and controls.…”
Section: Discussionmentioning
confidence: 99%